Fast food is not the only junk food: Consumption pattern of different types of junk food in adolescents of Aligarh - Faizi, Nafis; Mittal, Charul (Indian Journal of Child Health, 2018)
Background: Junk food is a term that is used for many types of food including the predominantly western - fast foods, as well as for local - street foods and instant foods. Objectives: The objectives of this study were to assess the consumption pattern of fast food, street food, and instant foods among adolescents and their correlation and to determine the preferred food among these, if there were no cost constraints. Materials and Methods: A cross-sectional school-based study was conducted in 13–15 years old adolescents from two schools of Aligarh. The study used pictorial examples to ascertain the prevalence of different types of food. Data were analyzed using SPSS-20. Spearman’s rho was applied to find correlations among the different food categories. Results: The consumption rate of fast food, street food, and instant food for twice or more times a week was 57.7%, 55.7%, and 46.1%, respectively. Furthermore, if money was not a restraint, the most favored food was fast food (44%). There is a significant correlation of consumption patterns of these foods. Conclusion: The unhealthy junk foods consumption includes not only the western fast foods which are ultra-processed but also Indian street foods rich in trans fats as well as instant foods. A more nuanced and comprehensive approach is needed to counter the hazards of the current junk food environment.